PARTISIPASI PEMILIK HPR TERHADAP PROGRAM PENCEGAHAN PENYAKIT RABIES DI DESA ABIANSEMAL DAN DESA BONGKASA PERTIWI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Luh Sri Widiantari; Made Pasek Kardiwinata (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2016)
Badung District, in the Province of Bali was found to have the highest HPR bite cases in 2011, with a total of 8111 cases. In the subdistrict level, Abiansemal had the highest case with 2199 cases. The purpose of this study was to describe the HPR owner participation towards rabies prevention programme at Abiansemal Subdistrict in Badung District. This study was a descriptive study with a cross-sectional approach. Systematic random sampling was used to identify the ninety samples in this study. Data collection used structured questionnaire and observation and then analysed by descriptive analysis. The results showed that 82,2% respondents in Abiansemal Village and 84,4% respondents in Bongkasa Pertiwi Village had vaccinated their dogs with VAR. About 82,2% respondents in Abiansemal Village and 91,1% respondents in Bongkasa Pertiwi Village left their dogs untied. All respondents in Abiansemal Village and Bongkasa Pertiwi Village (100%) had not registered their dogs. There were no differences in the HPR owner participation towards rabies prevention program between the area with high HPR bite cases and low HPR bite cases. It is recommended that the government of Badung District regulate and supervise the dog owner. Future research should address the completeness of Anti-Rabies Vaccination in dogs.